HOW CAN HISTORY LEARNING CONTRIBUTE TO CITIZENSHIP EDUCATION IN DUAL SUBJECTS SYSTEM? - CASE JAPAN - - EIJI FUJITA (Sriwijaya University Learning and Education International Conference, 2016)
HOW CAN HISTORY LEARNING CONTRIBUTE TO CITIZENSHIP EDUCATION IN DUAL SUBJECTS SYSTEM? - CASE JAPAN -